Penetrating the biofilm barrier: characterization of Escherichia phage vB_EcoS-TPF103dw and harnessing depolymerase to combat Shiga toxin-producing Escherichia coli O103 biofilm - Campos, David L.; Liao, Yen-Te; Harden, Leslie A.; Zhang, Yujie; Wu, Vivian C. H. (Frontiers in Microbiology, 2025)
IntroductionBesides Shiga Toxin-producing Escherichia coli (STEC) O157:H7, non-O157 STEC strains, such as O103, have been linked to outbreaks in meat, dairy, and produce. This study aimed to characterize and evaluate the newly isolated Tequintavirus phage, vB_EcoS-TPF103dw, as an intervention against STEC O103 biofilm.MethodsPhage vB_EcoS-TPF103dw isolated from chicken feces, was sequenced and biologically characterized. Antimicrobial activity was tested in vitro and against O103 biofilm on stainless steel. Biofilm disruption was examined by scanning electron microscopy (SEM).ResultsTPF103dw, belonging to the Tequintavirus genus, has a latent period of approximately 50 min, with an estimated burst size of 232 PFU/cell, and is stable over a wide range of pH (pH 5 to pH 10) and temperature (4 to 60 °C). Phage TPF103dw encoded four high-probability (>90%) depolymerase candidates. The results showed filtrate containing soluble phage-derived enzymes alone were sufficient to dismantle the extracellular polysaccharide layer, as confirmed by SEM. Phage application against STEC O103 biofilm on stainless-steel coupons for 30 min resulted in a significant STEC O103 reduction of 0.83 log CFU/coupon.DiscussionThe findings of this study provide insights into a novel Tequintavirus phage, vB_EcoS-TPF103dw, and demonstrate its genomic diversity, predicted depolymerase-encoding potential, stability under variable conditions, and antimicrobial efficacy against STEC O103 biofilms in vitro.